Development Of School Digitalization Program Through In-House Training To Improve Educational Services - Rejeki, Yulia Suci; Suhaenah, A; Sari, Yessy Yanita (Jurnal Mamangan, 2024)
The focus of this study is to develop a school digitalization program design through In-House Training (IHT) to improve educational services in Bintaro 12 State Elementary School. The hypotheses tested are 1) developing a school digitalization program design through In-House Training 2) testing the feasibility of the school digitalization program stages through In-House Training. Further, the study is conducted due to the need for school digitalization acceleration program which launched by the Ministry of Education and Technology, the data from supervision of school principals, the impact of teaching and learning after the pandemic, as well as social changes on students. Based on this situation, this study is designed to develop a school digitalization program through In-House Training for teachers in Bintaro 12 State Elementary School to improve educational services. This study implemented Research and Development (R&D) method using the Borg and Gall model. Data collection techniques were observation and questionnaires with survey methods. Data was collected through three instruments, namely material expert validation data, media expert validation and teacher trainer validation using the Guttman scale. The validation test to determine the effectiveness of the program was tested on students using a Likert Scale. The results of the material expert test regarding the IHT stages as a whole are 93.52% (very decent) while the results of the media expert test regarding the Quizizz and Canva application stages are 100% (very decent) and 77.78% (decent). For the results of the effectiveness of the program design on students, the score is 70.95%, which means it is in the good category. The results of this research were carried out six times by IHT. The final product developed can be used as a school digitalization program design through In-House Training to improve educational services and can also be a training reference for schools.